1990
DOI: 10.1007/bf01465913
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the whole-body distribution of PET radiopharmaceuticals, applied to 3-N-([18F]fluoroethyl)spiperone

Abstract: Using a multi slice whole body PET scanner PC4096-15WB, diagnostic measurements of the cerebral distribution of the D2 receptor ligand 3-N-([18F]fluoroethyl)spiperone were extended to quantify the biodistribution of this PET radiopharmaceutical. As a rotating line source was used for measured attenuation correction, transmission scans could be combined with emission scans even after injection of the tracer. Only 1% of the total administered dose (TAD) was found in the whole brain at 180 min, but the striatum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…The combination of advanced technology and biological tracers has generated new pathophysiological data, and it has been shown that the application of bioOffprint requests to: A. van Lingen logical tracers might benefit larger groups of patients (Camici et al 1986;Tillisch et al 1986;Di Chiro et al 1987;Strauss 1990). Therefore, it is attractive to image these tracers in the body with the generally available equipment, as has been reported by Hoeflin et al (1989), Herzog et al (1990) and Paul (1987).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of advanced technology and biological tracers has generated new pathophysiological data, and it has been shown that the application of bioOffprint requests to: A. van Lingen logical tracers might benefit larger groups of patients (Camici et al 1986;Tillisch et al 1986;Di Chiro et al 1987;Strauss 1990). Therefore, it is attractive to image these tracers in the body with the generally available equipment, as has been reported by Hoeflin et al (1989), Herzog et al (1990) and Paul (1987).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the abdomen will be difficult to evaluate with these tracers (Herzog et al 1990). Further reviews of the D2R reporter gene are to be found in previous publications (Herschman 2004a(Herschman , 2004b.…”
Section: Dopamine 2 Receptor (Hd2r)mentioning
confidence: 98%
“…An example of an acquisition scheme which was performed for the 18 F-labelled D2-receptor ligand [ 18 F]-fluoro-ethyl-spiperone is shown in Fig. 3 [8].…”
Section: Biodistribution Measurement Of Positron Emittersmentioning
confidence: 99%